Relation of fertilization and the quality of agricultural products (Research, Society and Development, 2022)
In the current agricultural mart with high production and demand, quality is the main decisive factor among consumers. Therefore, in order to obtain satisfactory quality and production characteristics, a balanced supply of water and nutrients during plant development is essential. In this work, we seek the results of research on the relationship between nutrition and quality of agricultural products. It is concluded that sustainable water and fertilizer management strategies can improve the productivity and quality of raw materials, and it is also necessary to understand the individual physiological functions of each nutrient and the ecological and climatic characteristics of production to make decisions that guarantee high-quality production.